The Archaeology of the Military Orders: The Material Culture of Holy War. Issue 1 (2nd January 2018) - Pluskowski, Aleks
Abstract : THIS PAPER reviews the current state of research into the archaeology of the military orders. It contrasts the advances made by historians and archaeologists, with the latter continuing to focus on the particularism of individual sites, with an emphasis on architectural analyses. Historians have contributed new insights by adopting a supranational approach. This paper argues that archaeologists can build on this by adopting a more problem-oriented, comparative approach. Drawing on examples from frontier and heartland territories, archaeological approaches are subdivided into material investment, material identity and cultural landscapes, to place sites of the military orders within long-term, multi-scalar contexts. This contributes to a broader social and economic understanding of the orders, who contributed significantly to urbanisation, rural development and trade, and invested in material expressions of their authority and ideology. The paper concludes that more holistic, interregional approaches will move the archaeological study of the military orders forward.